Pengaruh Brand Experience Dan Brand Image Terhadap Brand Loyalty Yang Dimediasi Dengan Brand Equity Handphone Xiaomi Di Solo Raya - Muhammad Nur Mutashim Billah Al Muhatarom; Wafiatun Mukharomah (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2023)
This study aims to analyze the effect of brand experience and brand image on brand loyalty mediated by brand equity on Xiaomi mobile phones in Soloraya. This research is included in quantitative research. The population in this study is xiaomi mobile phone customers in Soloraya. The sample used in this study was 150 respondents. The sampling technique used was non-probability sampling and the approach used in determining the sample was purposive sampling. Sources of data used in this study using primary data. Methods of data collection using a questionnaire. Data analysis using Smart PLS 3.0 application. The results of the analysis in this study show (1) Brand experience has a significant positive effect on brand equity (2) Brand image has a significant positive effect on brand equity (3) Brand equity has no significant effect on brand loyalty (4) Brand experience has no significant effect on brand loyalty (5) Brand image has no significant effect on brand loyalty (6) Brand experience has no significant effect on brand loyalty with brand equity mediation (7) Brand image has no significant effect on brand loyalty with brand equity mediation.